Penerapan Pencatatan Anggaran Biaya Menggunakan Microsoft Excel dan Realta Global System - Wati, Hernawati; Restu Alpiansah (Jurnal Ilmiah Pengabdian dan Inovasi, 2024)
Microsoft Excel and Realta Global System (RGS) are essential tools in financial management and inventory control within the hospitality industry. This KKN (community service) report focuses on these tools' application at Qunci Villas Hotel in Lombok, aiming to improve operational efficiency. The topic was chosen due to the critical role of accurate financial and inventory management in ensuring smooth hotel operations and customer satisfaction. The study employed the Participatory Action Research (PAR) method, which involved active participation from the hotel's staff and management in identifying issues, developing solutions, and evaluating outcomes. Through detailed observations and interviews, the project identified key challenges in the processes of recording Store Requisitions (SR), creating Purchase Orders (PO), and receiving goods. The findings highlighted the need for enhanced training on Excel and RGS usage, better system integration, and improved data management practices. Implementing these recommendations is expected to lead to more accurate data entry, better decision-making, and increased overall efficiency. The results underscore the importance of leveraging technology in financial and inventory management and provide a practical framework for other hotels aiming to optimize their operations. This study demonstrates that participatory approaches can significantly improve organizational processes and employee engagement.